A randomized controlled trial of different young child formulas on upper respiratory and gastrointestinal tract infections in Chinese toddlers. Issue 7 (12th June 2020) - Leung, Ting F.; Ulfman, Laurien H.; Chong, Marc K. C.; Hon, Kam L.; Khouw, Ilse M. S. L.; Chan, Paul K. S.; Delsing, Dianne J.; Kortman, Guus A. M.; Bovee‐Oudenhoven, Ingeborg M. J.
Abstract: Background: Bioactive proteins and human milk oligosaccharides (HMOs), important ingredients in breast milk, that protect against infections are lacking in young child formula (YCF). This study investigated the effects of new YCFs on respiratory and gastrointestinal infections in toddlers. Methods: Four hundred and sixty one healthy Chinese children aged 1‐2.5 years were recruited in this randomized, controlled, double‐blind, parallel‐group clinical trial of different YCFs. They were randomly assigned to either standard milk formula (YCF‐Ref) or one of three new YCFs containing bioactive proteins and/or the HMO 2′‐fucosyllactose (2′‐FL) and/or milk fat for six months. Primary outcomes were incidence of upper respiratory tract infection (URTI) and duration of gastrointestinal tract infections (GITI). Results: There were no significant between‐group differences in primary outcomes. For secondary outcomes, subjects receiving 2′‐FL‐supplemented YCF had longer URTI. Subjects receiving YCF supplemented with milk fat and intact bioactive proteins, and 2′‐FL at levels found in breast milk, had more GITI episodes and shorter time to first GITI but similar effects on URTI duration than YCF‐Ref recipients. No effects on URTI and GITI were observed in toddlers receiving YCF with bioactive proteins at lower levels than breast milk. Occurrence of adverse events and anthropometry were similar in all groups. Conclusions: All three YCFs supplemented with different combinations of intact bioactive proteins, 2′‐FL, and milk fat are safe in toddlers. No difference is detected among YCFs on URTI incidence and GITI duration. Further studies are needed to verify these findings especially in infants who may benefit most from the immune‐boosting effects of bioactive proteins and HMOs.